Numerical modeling and experimental validation of air-side forced convection on a Wire-on-tube condenser for a domestic refrigerator - Sahnali, Funda Erdem; Atayilmaz, S. Ozgur; Gemici, Zafer (TAYLOR & FRANCIS INC, 2025)
In this study, the effects of various parameters on the air-side performance of a condenser used in a domestic refrigerator were investigated numerically and experimentally. A new condenser design with streamlined eye and kammtail tube shapes was studied to delay flow separation. The kammtail form was utilized in a wire-and-tube heat exchanger for the first time in this work instead of traditional round or elliptical geometry. Different design parameters were studied for the outer tube height (3, 3.5, 4, 4.5, and 5 mm), aspect ratio of the tube (1.5, 2, and 2.5), tube pitch (20 and 15 mm), tube arrangement (inline and staggered), and tube shapes (eye, kammtail, and ellipse forms) to improve the air-side performance. The model was validated using experimental data based on a performance test setup and wind tunnel measurements conducted at different air velocities. The impact of tube shape and tube dimensions on the convection coefficient and pressure drop were found to be dominant due to delayed flow separation and reduction in the recirculation area. The results showed that, for a similar heat-transfer rate, the total tube surface area was reduced by 7%, the convection coefficient was increased by 9.4%, and the static pressure drop was decreased by 27% with the new Kamm tail-form design of 3 x 6 mm compared to the respective values of the original condenser. In addition, for a similar air-side performance, decreasing the tube pitch from 20 to 15 mm resulted in subsequent decreases of up to 30% in the heat exchanger volume. When the tube arrangement was changed from inline to staggered, the convective coefficient increased by 23% and the pressure decreased by 14%. The numerical results were in good agreement with the experimental results, showing errors of less than 10% for air pressure drop and less than 9% for heat-transfer capacity.
Keywords: Computational fluid dynamics; experimental validation; GLM-ANOVA analysis; response optimization; tube shapes; wire-on-tube condenser; HEAT-TRANSFER CHARACTERISTICS; WAVY FIN; EXCHANGER; FLOW; PERFORMANCE; NUMBER; BUNDLES; Thermodynamics; Mechanics